PENGARUH METODE PEMBELAJARAN DAN KECERDASAN INTERPERSONAL TERHADAP HASIL BELAJAR SEJARAH SISWA SMA - IMANITA, MYRISTICA (JURNAL PENDIDIKAN SEJARAH, 2014)
This study aimed to determine the effect of learning methods and studentâs interpersonal intelligence on the outcome of history learning on the students. This research is quantitative research using design treatment by level 2x2. The research date was taken from the observation, tests and questionnaires. The results showed that(1) history learning outcome of students who follow STAD instructional methods higher than students who follow conventional instructional methods, (2) there is interaction effect between instructional methods and interpersonal intelligence on history learning outcome of students, (3) history learning outcomesof students who follow STAD instructional method with high interpersonal intelligence, higher than students who follow conventional instructional method, (4)history learning outcomes of students who follow STAD instuctional methods with low interpersonal intelligence, lower than students who follow conventional instructional methods.Keywords: History learning outcome, instructional method, interpersonal intelligence